1994
DOI: 10.1002/neu.480251205
|View full text |Cite
|
Sign up to set email alerts
|

Expression of trk and neurotrophin mRNA in dorsal root and sympathetic ganglia of the quail during development

Abstract: The nerve growth factor (NGF) family of neurotrophins exerts effects by binding to products of the trk family of proto-oncogenes. We examined the expression of both trk and neurotrophin mRNA during the entire range of development of quail dorsal root ganglia (DRG) and sympathetic ganglia (SG) using in situ hybridization and reverse transcriptase-polymerase chain reaction (RT-PCR). TrkC mRNA was present in neurons or their precursors from the time of formation of DRG (stage 18, embryonic day 2.5 [E2.5]) and thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
0
1

Year Published

1996
1996
2009
2009

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 70 publications
4
26
0
1
Order By: Relevance
“…This is consistent with the observation that NGF supports the survival of chick sympathetic ganglia at later stages of development, but has little effect on the survival or proliferation of neurons at early stages. Although p140trk mRNA has been observed in quail sympathetic ganglia at embryonic day 8 by in situ hybridization (Zhang et al, 1994), the size of the transcript(s) that islare present has not been examined in any avian species. The 2.7 kb pl4OtTk transcript obtained from embryonic chick sympathetic ganglia in our studies agrees with the size of the transcript reported in the rat (2.9 kb; Meakin et al, 1992).…”
Section: Discussionmentioning
confidence: 98%
“…This is consistent with the observation that NGF supports the survival of chick sympathetic ganglia at later stages of development, but has little effect on the survival or proliferation of neurons at early stages. Although p140trk mRNA has been observed in quail sympathetic ganglia at embryonic day 8 by in situ hybridization (Zhang et al, 1994), the size of the transcript(s) that islare present has not been examined in any avian species. The 2.7 kb pl4OtTk transcript obtained from embryonic chick sympathetic ganglia in our studies agrees with the size of the transcript reported in the rat (2.9 kb; Meakin et al, 1992).…”
Section: Discussionmentioning
confidence: 98%
“…The neurotrophin receptors TrkA, TrkC, and p75 NTR are all expressed in sympathetic neurons throughout development (24,(47)(48)(49)). NT3 appears to act on a population of cells expressing both TRKA and TRKC.…”
Section: Discussionmentioning
confidence: 99%
“…At E4.5, 23% of the nascent DRG cells are trkA-positive. trkA mRNA expression is detectable later by ISH in quail embryos and remains consistently at 73% of Hu-positive cells from E6 to E15, the last stage analysed in the study of Zhang et al (1994). trkB expression in chick DRG begins at E3; by E4.5, 47% of the nascent DRG cells are trkB-immunoreactive (Rifkin et al 2000).…”
Section: Developmental Expression Of Genes Specifying Neuronal Diversitymentioning
confidence: 96%